THE VARIATION OF BALINESE CULTURAL TERMS IN BANGLI MEDIA TOURISM PROMOTION - Kadek Ayu Ekasani; I Gusti Ayu Agung Dian Susanthi; Ni Luh Gede Liswahyuningsih (Institut Pariwisata dan Bisnis Internasional, 2016)
There are so many tourism texts in English, so that ranslation study and tourism is very close to each other. Bali, as tourist destination is popular with its culture and tradition, Bali has eight regencies which are very interesting to visit. One of them is Bangli which is very popular with tourism destination. It has its own media to introduce its culture, tradition, etc. This writing deals with the process of meaning transfer in Balinese cultural term in Bangli Media Tourism Promotion.. The data used in this study is taken from Bangli’s booklet of tourism promotion which represent the Balinese cuture and tradition. The componential analysis which relates to semantics theory is used in this study, this theory helps to understand about the meaning of the Balinese cultural terms. The theories applied in this study are semantic components by Larson (1998) and the intercultural communication by Scollon (1995). The analyzed data is presented informally (in the form of words and sentences) and formally (the used of symbol). There are some cultural terms which discussed in this study: kulkul—Balinese bell; banjar—community group; pelinggih—shrine; kain putih—white fabrics; lontar—old manuscript; purusa-male; pradana-female.